The relevance of aging-related changes in brain function to rehabilitation in aging-related disease - Crosson, Bruce; McGregor, Keith M.; Nocera, Joe R.; Drucker, Jonathan H.; Tran, Stella M.; Butler, Andrew J. (Frontiers in Human Neuroscience, 2015)
The effects of aging on rehabilitation of aging-related diseases are rarely a design consideration in rehabilitation research. In this brief review we present strong coincidental evidence from these two fields suggesting that deficits in aging-related disease or injury are compounded by the interaction between aging-related brain changes and disease-related brain changes. Specifically, we hypothesize that some aphasia, motor, and neglect treatments using repetitive transcranial magnetic stimulation (rTMS) or transcranial direct current stimulation (tDCS) in stroke patients may address the aging side of this interaction. The importance of testing this hypothesis and addressing the larger aging by aging-related disease interaction is discussed. Underlying mechanisms in aging that most likely are relevant to rehabilitation of aging-related diseases also are covered.